Prevalence and correlates of premature ejaculation in a primary care setting: a preliminary cross-sectional stud - Tang, W.S.; Khoo, E.M. (Elsevier, 2011)
INTRODUCTION: Premature ejaculation (PE) is common. However, it has been underreported and undertreated.